The influence of sociodemographic factors on parental involvement in academic lives of undergraduate students at University of Jaffna - Dhanakgedra, P.M.; Deepashika, K.A.T.M. (University of Jaffna, 2024)
Introduction: Parental involvement in the academic lives of undergraduate students is a multifaceted phenomenon influenced by various factors. As students navigate their educational journey, the level of engagement from parents can play a pivotal role in shaping outcomes. Parental involvement takes on various forms of offering guidance and emotional support and providing financial resources. Well-established parental support during the university years can positively influence on academic achievement and personal development. Objective: To assess the influence of sociodemographic factors on parental involvement in the academic lives of undergraduate students at University of Jaffna. Methodology: A descriptive cross-sectional study was conducted among 426 undergraduates, who were studying in the selected faculties and units at the University of Jaffna from January 2023 to November 2023. The relevant data was collected using a self- administered questionnaire and data analysis was done using SPSS 25. To assess the significance of sociodemographic factors on parental involvement levels among University of Jaffna students, a Chi-square test was conducted. Results: Among the 426 participants, nearly two-thirds of them were females (62.2%) and the majority of them (63.6%) were under the age of 24 years. The age range of the participants was 21 to 28 years and the mean age of 23.45 (SD±1.832). Tamil: Sinhala students’ ratio was 3:1. Among the 426 participants, 41.5% were staying at the University Hostel, 34.5% were staying in the Boarding House, and 23.9% were staying with their parents. More than half of them (58.5%) had a good level of parental involvement while 24.2% had an excellent level of parental involvement. Among sociodemographic factors, gender, ethnicity, faculty, academic year, and current residence were significantly associated (p<0.05) with parental involvement. Conclusion: Parental involvement of the parents of these populations is very high. The study recommends that parental involvement can be focused on establishing clear communication channels, organizing orientation programs for parents, and creating platforms for ongoing collaboration between parents and the university to support students’ holistic.
Keywords: Parental involvement; Academic lives; Undergraduates; University of Jaffna